2007
DOI: 10.1681/asn.2007040402
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in End-Stage Renal Disease Rates in HIV Infection versus Diabetes

Abstract: Few studies have compared the incidence of end-stage renal disease (ESRD) among individuals with the human immunodeficiency virus (HIV) and diabetes. We followed a national sample of 2,015,891 US veterans over a median peroid of 3.7 years for progression to ESRD. The age-and sex-adjusted incidence of ESRD (per 1000 person-years) among HIV-infected black patients was nearly an order of magnitude higher than among HIV-positive white patients, almost twice that of diabetic whites, and similar to that among diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 35 publications
8
78
10
Order By: Relevance
“…Diabetes is already a traditional risk factor for chronic kidney disease in the general population. Several studies had demonstrated that diabetes plays an important role in kidney disease in the HIV infected patients [3,10,20]. Krawczyk et al in the United States (p=0.259) and Flandre et al in France (p=0.30) did not find an association between diabetes and chronic kidney failure among HIV infected patients [4,18].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 97%
See 1 more Smart Citation
“…Diabetes is already a traditional risk factor for chronic kidney disease in the general population. Several studies had demonstrated that diabetes plays an important role in kidney disease in the HIV infected patients [3,10,20]. Krawczyk et al in the United States (p=0.259) and Flandre et al in France (p=0.30) did not find an association between diabetes and chronic kidney failure among HIV infected patients [4,18].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 97%
“…Emem studying kidney disease defined by the presence of proteinuria positive dipstick and/or serum creatinine higher than or equal to 132 μmol/L (15 mg/L) in seropositive-HIV patients in Nigeria had found a prevalence of 38% [9]. Similarly, in Uganda, Andia had found a prevalence of chronic kidney disease to 48.5% in Patients with HIV [10].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 99%
“…A prevalence of CRF in different populations of HIV-infected people (whether or not treated, controlled or otherwise) may be as high as 5% to 25% (188)(189)(190). Highly active anti-retroviral therapy (HAART) treatment has not eliminated HIV-specific renal disease, the HIV-associated nephropathy (HIVAN), which is responsible for 40% to 60% of the histological renal disease (191), or the need for transplantation in HIV-infected patients (192).…”
Section: Cysc and Acquired Immunodeficiency Syndrome (Aids)mentioning
confidence: 99%
“…1 The reported prevalence of CKD in patients infected with HIV in North America and Europe ranges from 4.7% to 9.7%, and higher rates have been reported when CKD is defined by either estimated glomerular filtration rate (eGFR) or proteinuria. [2][3][4] HIV infection is a well-established risk factor for CKD and endstage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%